Practices and Perceptions Regarding Pain and Pain Management during Routine Childhood Immunizations: Findings from a Focus-Group Study with Nurses Working at Toronto Public Health, Ontario - Andrew Kikuta; Fauzia Gardezi; Vinita Dubey; Anna Taddio (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Despite the availability of a variety of evidence-based interventions, it has previously been reported that the majority of infants and children undergo vaccine injections without the benefit of analgesia. Nurses in public health administer a substantial number of injections; however, their attitudes and practices surrounding acute pain during vaccine injections have not been previously explored.